Effects of biochar application on sugarcane growth and physiology under combined saline and drought stress conditions - Ngoc-Thang Vu; The-Khuynh Bui; Thi-Tuyet-Cham Le; Dong-Cheol Jang; Thai-Hoang Dinh (Plant Production Science, 2025)
Drought and salinity intrusion have been constraints on sugarcane production in coastal areas. Improving water and nutrient uptake and reducing sodium chloride accumulation by applying biochar could be an effective way to solve the problem. A pot experiment was done following a Split-plot design with three replications under greenhouse conditions. We applied four irrigation schedules for the main-plot treatments to maintain different growing conditions, including control, drought, saline, and combined saline-drought (saline stress followed by drought stress). The sub-plot factor was three application rates of oak biochar of 0, 5, and 10 tons ha−1. Here, we found that single stress conditions reduced sugarcane growth for plant height, stalk diameter, leaf number, leaf size and area, total biomass, root mass, and root volume. Physiological parameters, including leaf SPAD, the quantum efficiency of photosystem II, ion leakage, and relative water deficit, also dropped under stress effects. Our results also found that the combined saline and drought stress induced more damage than either stress alone and led to a greater reduction in sugarcane growth. Applying biochar positively affected sugarcane’s growth and recovery after these stress periods. The 10 tons of biochar ha−1 rate was the optimum dose for sugarcane production in drought and saline-affected areas.